Impact of Microfinance on Women Empowerment: A Study Based Upon Micro Finance Institutions of Kanchanpur, Nepal - Tiwari, Nisha Bhatt (Far Western Review, 2023)
This study explores the transformative impact of microfinance on the lives of women in Kanchanpur, emphasizing the role of microcredit in fostering economic self-reliance and social empowerment. The research aims to analyze the contributions of women entrepreneurs, evaluate socio-economic activities, and assess the effectiveness of microfinance in improving living standards. The investigation focuses on the ability of group-based micro loans to alleviate poverty, address socio-economic vulnerability, and foster the formation of social capital among women in Kanchanpur. Using a descriptive survey research method with both quantitative and qualitative paradigms, the study randomly selects 350 informants from five microfinance institutions in Kanchanpur. Data collection involves schedules, focus group discussions, interviews, and field observations. The research framework includes control, dependent, and independent variables, with four criteria—access, creation, and control over private resources; decision-making freedom at home; self-confidence in socio-economic activities; and status in the community and family— used to examine the impact of microfinance on women’s empowerment. The empirical findings reveal that small loans provided by microfinance institutions stimulate income-generating activities among rural women, leading to improvements in their well-being and socio-economic status. The study concludes that women owning and utilizing microcredit positively influences their decision-making abilities at home, contributing to an overall elevation of their socio-economic status. The results suggest a need for government initiatives to facilitate rural women through targeted microcredit schemes, thereby further promoting women’s empowerment in Kanchanpur.